The complete story of Tishrei - Mindel, Nissan (Merkos L'inyonei Chinuch, 1982)
A comprehensive presentation of the events of Tishrei, the first month of the Jewish calendar, which includes such highlights as Rosh Hashanah, Yom Kippur, and Sukkot.